Glacial Isostatic Adjustment of the Laurentian Great Lakes Basin: Using the Empirical Record of Strandline Deformation for Reconstruction of Early Holocene Paleo-Lakes and Discovery of a Hydrologically Closed Phase - Michael Lewis, C.F.; Blasco, Steve; Gareau, Pierre (Géographie physique et Quaternaire, 2005)
AbstractIn the Great Lakes region, the vertical motion of crustal rebound since the last glaciation has decelerated with time, and is described by exponential decay constrained by observed warping of strandlines of former lakes. A composite isostatic response surface relative to an area southwest of Lake Michigan beyond the limit of the last glacial maximum was prepared for the complete Great Lakes watershed at 10.6 ka BP (12.6 cal ka BP). Uplift of sites computed using values from the response surface facilitated the transformation of a digital elevation model of the present Great Lakes basins to represent the paleogeography of the watershed at selected times. Similarly, the original elevations of radiocarbon-dated geomorphic and stratigraphic indicators of former lake levels were reconstructed and plotted against age to define lake level history. A comparison with the independently computed basin outlet paleo-elevations reveals a phase of severely reduced water levels and hydrologically-closed lakes below overflow outlets between 7.9 and 7.0 ka BP (8.7 and 7.8 cal ka BP) in the Huron-Michigan basin. Severe evaporative draw-down is postulated to result from the early Holocene dry climate when inflows of meltwater from the upstream Agassiz basin began to bypass the upper Great Lakes basin.